Does market competition dampen environmental performance? Evidence from China - Duanmu, Jing‐Lin; Bu, Maoliang; Pittman, Russell (Strategic Management Journal, 2018)
Research Summary : Departing from the extant literature, which assumes that firms pursue strong environmental performance as a differentiation strategy, we analyze the general relationship between firms’ competitive strategy and their response to heightened market competition. We find that, using a large sample of Chinese manufacturing firms between 2000 and 2005, intensified market competition has an overall negative impact on firms’ environmental performance. The negative impact is exacerbated in firms adopting a cost‐leadership strategy, but is attenuated in those adopting a differentiation strategy. The results emphasize the importance of including an examination of the particular competitive strategies chosen by firms in seeking to understand the impact of intensified market competition. Managerial Summary : Advocates of corporate social responsibility (CSR) have long argued for the differentiation role of CSR. However, managers may be misguided if the assumed benefits of differentiation critically depend on certain presumptions. In the Chinese context and focusing on the environmental dimension of CSR, our study finds a negative relationship between market competition and corporate environmental performance. It suggests that firms, to a large extent, cannot escape competition via environmental differentiation. Managers should therefore be cautious about the value of strategic investment in CSR as a viable competitive device.